What’s Wrong with the Policy of Releasing Patient Medical Information at Regional Public Hospital X - Dimas Aulia Savitri; Antono Suryoputro; Farid Agushybana; Gunchmaa Nyam (Universitas Ahmad Dahlan, 2022)
Background: The release of medical information to third parties is the responsibility of the health facility to protect the health information contained in it from being damaged, lost, falsified data, and illegal access. Therefore, health facilities must have policies that regulate the system for releasing patient medical information to third parties. This study aims to analyze the policy of the patient's medical information release system in RSUD X. Method: This research is a descriptive study with a qualitative approach, through in-depth interviews and observation techniques. The informants in this study amounted to 12 people, namely the leadership of the hospital, the manager of medical services, the head of the medical record section, and the DPJP. Results: The results of this study indicate that RSUD X already has a policy regarding the system of releasing medical information to third parties but the release activities in the field it is not following the policy. This is because communication such as socialization from the leadership is still lacking so policy actors still do not know about the policy. The leadership has also never carried out monitoring and evaluation related to the release activity so the leadership does not know that other factors cause the policy not to work. Conclusion: The release of medical information to third parties already has a policy set out in the sop, but in its implementation, it is not following the existing sop due to the lack of socialization related to the sop to the discharge officers, the absence of monitoring and evaluation of the discharge activities that have been running at RSUD X. Also, the social attitudes of the community that are considered to have the most influence on the activities of releasing patient medical information in RSUD X.